5x+(-8)=(-2x)+(-6)

Simple and best practice solution for 5x+(-8)=(-2x)+(-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+(-8)=(-2x)+(-6) equation:


Simplifying
5x + (-8) = (-2x) + (-6)
5x + -8 = (-2x) + (-6)

Reorder the terms:
-8 + 5x = (-2x) + (-6)
-8 + 5x = (-2x) + -6

Reorder the terms:
-8 + 5x = -6 + (-2x)

Solving
-8 + 5x = -6 + (-2x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(2x)' to each side of the equation.
-8 + 5x + (2x) = -6 + (-2x) + (2x)

Combine like terms: 5x + (2x) = 7x
-8 + 7x = -6 + (-2x) + (2x)

Combine like terms: (-2x) + (2x) = 0
-8 + 7x = -6 + 0
-8 + 7x = -6

Add '8' to each side of the equation.
-8 + 8 + 7x = -6 + 8

Combine like terms: -8 + 8 = 0
0 + 7x = -6 + 8
7x = -6 + 8

Combine like terms: -6 + 8 = 2
7x = 2

Divide each side by '7'.
x = 0.2857142857

Simplifying
x = 0.2857142857

See similar equations:

| 51/4/32/3 | | -4x-4(17+2x)=16 | | 5b^3+34b^2-7b=0 | | 8+r=(-7) | | x+3(-6)=-16 | | x/16-5/8=(x+6)/8 | | 7/10x=84 | | 10(-16-3y)+6y=-16 | | 7+r=(-3) | | y=1/3*0.3333-2 | | 6w^4*x^2-8u^2*x/4x^3 | | (-2)+r=8 | | 2(p-1)=3p+2 | | y=1/3(-2)-2 | | y=1/3(2)-2 | | z^2-4z-8=0 | | 4x-4=2x-34 | | y=-2(-3)-8 | | -10x^2+9x+9= | | 7/12x=35 | | 3x+7=-2-8 | | 2r-6=8 | | 4x^2-25x+25= | | (x-9)2=49 | | -3(5x+12)=-18x-15 | | -1924*x=-962 | | .05x+.04y=119 | | .05x+.04y=252 | | 0.2x^2+4x-6=0 | | -2x^2+20x-48= | | -2t+2x=9 | | 3(g-5)=2(q+5) |

Equations solver categories